Industrial Heritage and Citizen Participation: The UNESCO World Heritage Site of Ivrea, Italy - Matilde Ferrero; Martha Friel; Erica Meneghin; Mariangela Lavanga (Urban Planning, 2024)
The article explores the dynamics of community involvement in managing the UNESCO World Heritage Site of Ivrea, Italy, designated as the “Industrial City of the 20th Century” in 2018. Ivrea is known for its historical connection to the Olivetti factory, whose existence shaped the town’s material and immaterial identity. The UNESCO-designated area in the north of the city features a mix of diverse buildings from the 1930s to the 1960s, serving various purposes and a variety of cultural activities. The research, commissioned as part of a larger project for updating the Site Management Plan by the Municipality of Ivrea, the managing authority of the UNESCO Site, aims to critically employ participatory approaches in the Management Plans of industrial heritage sites, analyse their role in preserving industrial heritage, and identify a new future for the city where cultural and creative industries play a vital role, or, in other words, to develop the site of Ivrea as a permanent cultural cluster. By employing an action-research methodology rooted in multidisciplinary and participatory approaches, this study focuses on the key role of residents and their connection to the industrial cultural heritage and the city to envision the site’s future. Initial findings from semi-structured interviews reveal a limited awareness of the Site Management Plan in the community and underscore the need for enhanced participatory governance. The article highlights how the collaborative efforts of stakeholders, particularly youth, yield innovative ideas, paving the way for social advancement, economic sustainability, and local promotion. Ultimately, this study envisions the UNESCO World Heritage Site as a central component of the city’s identity and a catalyst for the well-being of the involved communities.